Implementation of Religious Character Education in An Understanding of Noncorruption Education in Elementary School / Implementasi Pendidikan Karakter Religius dalam Upaya Pemahaman Pendidikan Anti Korupsi di MI - Nurlaeli Nurlaeli; Mardiah Astuti; Tutut Handayani (STAI Ma'had Aly Al-Hikam Malang, 2020)
The role of education condemned to prepare people who are competitive and free of corruption. The purpose of this study describes the implementation of the religious character education program in MI, the result of the implementation of religious character education program in MI, and the inhibitory factor and supporting factors for the application of religious character education in MI. This study used a qualitative approach. The results of his research, 1) program conducted by Madrasah is, prayer kalicesadyj in Congregation, BTA, Tahfidz Qur'an, habituation of discipline, honest, responsibilities and posters anti-corruption, 2) results in terms of behavior fostering confidence, honest attitude, dare to perform, able to cooperate well, have social responsibility and care. 3) Self-supporting and social factors, constraints in the implementation of internal and external. Solution of the obstacles faced is the solution, establish good communication between the school with the parents, evaluate every program that has been done by involving teachers and parents/guardians, socializing the parents/guardians about the implementation of religious character education activities to be supported also when at home, in order to be carried out with maximum.